Optimization and Test of Metallic Seal Structure for High-Speed Bit - Liu Yang; Li Wenqi; She Yang Zhou (Shiyou jixie, 2025)
The influence of bit protective gasket on seal structure has been less studied， and there is a lack of structural optimization and experimental study results of gasket. In this paper， test and finite element methods were combined to analyze the influences of parameters such as press-fit force and specific pressure of end face on the mechanical behaviors and sealing performance of metallic seal system as well as the defects of the existing gasket structure. Then， a new type of gasket was designed， and the original structure was improved. The results show that compared with the original gasket structure， the new one has an increased effective contact area with the energy supply ring and the end face of metallic seal ring， relatively uniform stress distribution with less stress concentration， and smooth deformation. Moreover， the contact pressure meets the requirements for sealing function at the maximum displacement， and wear can also be effectively reduced. The mechanical performance test and unit leakage test results show that the new gasket structure is qualified for the sealing of high-speed roller cone bit. The study results provide theoretical and test support for improving the sealing performance and service life of high-speed bits.